Self-reported symptom occurrence and distress, and psychological well-being after liver transplantation – a descriptive cross-sectional study of Danish recipients - Dengsø, Kristine Elberg; Knudsen, Andreas Dehlbæk; Møller, Dina Leth; Forsberg, Anna; Nielsen, Susanne Dam; Hillingsø, Jens (Frontiers in Psychology, 2024)
Introduction Symptom distress and impaired psychological well-being after liver transplantation may lead to limitations in everyday activities and lowered health-related quality of life. The aim of this nationwide, descriptive, and cross-sectional study was to explore self-reported symptom occurrence and distress, among Danish liver transplant recipients, and their association with self-reported psychological well-being as well as demographic, and clinical characteristics. Methods Liver transplant recipients transplanted from 1990 to 2022 were included. All recipients were asked to complete the Organ Transplant Symptom and Wellbeing instruments consisting of two instruments measuring self-reported symptom occurrence and distress, respectively, as well as self-reported psychological well-being by the Psychological General well-being instrument. Results Of 511 invited recipients 238 responded: 116 women and 122 men with a median post-transplant follow-up of 7.5 years (IQR 3.6–14.2 years). The most common single symptoms reported were decreased libido (18%), diarrhea (10%), and headache (8%). Sleep problems were the most common transplant-specific domain. 41% of the recipients reported poor psychological well-being, especially those who had undergone transplantation within the last 5 years, women, and younger recipients. Discussion In the interest of equity, the fact that women reported a higher level of symptom distress than men requires attention. Research on symptom management support is warranted with interventions focusing on how to alleviate symptom distress, which might increase long-term survival, which has not improved in recent decades.